Degradation of cellulose within the gastrointestinal tract in man. Issue 8 (August 1984) - Kelleher, J; Walters, M P; Srinivasan, T R; Hart, G; Findlay, J M; Losowsky, M S
Abstract : 14C-labelled cellulose was administered orally to 10 subjects without gastrointestinal disease and its absorption measured by faecal 14C excretion and 14CO2 in expired air. A mean of 57.2% of oral cellulose was excreted in the faeces and up to 14% (mean 7.5 +/- 4.4 1SD) of faecal radioactivity was water soluble. Whole gut transit time did not correlate with the quantity of 14C-cellulose excreted in the faeces. A significant quantity of 14CO2 appeared in the expired air as early as 30 minutes after administration of the labelled cellulose. The cumulative excretion of 14CO2 varied from 7.6-32.2% of the administered radioactivity but did not correlate with faecal 14C excretion. The present data show that a significant quantity of oral cellulose is metabolised within the human gastrointestinal tract and appears in the expired air as 14CO2.